Das Verhältnis der tages- zur jahreszeitlichen Temperaturschwnakung - Paffen, Karlheinz (ERDKUNDE, 1967)
Arising from an unpublished world map, on which more than 100 of C. Troll's thermo-isopleth diagrams were accurately positioned, the author had the idea of also areally representing in exact numerical terms the relationship of diurnal to annual variations in temperature which are available for one station within each thermo isopleth diagram (Fig. 1). The result is presented on a world map (Suppl. Ill) on which the isarithms represent the relationship of diurnal to annual variation Ts/Js =Qs and polewards the line of equilibrium 1 the reciprocal value (Js/Ts =Qr). With the help of a nomogram (Fig. 2) and the author's world map of aperiodic diurnal changes (Erdkunde XX/4, Suppl. VIII) or of a map of annual variations we can thus easily determine the corresponding Ts and Js values for almost any place on earth (e. g. Fig. 3). The map shows in the central parts of the continents a pattern of isarithms parallel to lines of latitude, which show a broadly similar characteristic ordering in three continental meridional profiles from Pole to Pole (Fig. 4). The explanation of this is given by the mean value curves for Js and Ts worked out from the same meridional profiles (Fig. 5). Over the oceans, where Js is probably greater everywhere than the very small daily changes (1-2?) here (Fig. 5), the lack of adequate Ts values does not allow the construction of any isarithms. The maritime isarithms shown on the world map are based only on island values. Apart from the sea, the deviant behaviour of the Qs and Qr isarithms in mainland coastal areas also becomes under standable. We can recognise on the world map a contrary east and west coast effect in similar latitudes as a portent of changing climatic zones. The world map of the relationship between diurnal and annual variations of air temperature, as the examples show, allows a very complex discussion of planetary, regional and local climatic problems. It delivers, if not in detail, opportunities for delimiting and characterising climatic zones and regions (inner continental parts of the line of equilibrium as the boundary of the Tropics). Finally, the map is also a key to anthropo-climatological problems (e. g. freezing in the warm tropics where daily temperature variations are large although annual variations are small).